2015
DOI: 10.1088/1748-0221/10/02/p02013
|View full text |Cite
|
Sign up to set email alerts
|

DMAPS: a fully depleted monolithic active pixel sensor—analog performance characterization

Abstract: Monolithic Active Pixel Sensors (MAPS) have been developed since the late 1990s based on silicon substrates with a thin epitaxial layer (thickness of 10-15 µm) in which charge is collected on an electrode, albeit by disordered and slow diffusion rather than by drift in a directed electric field. As a consequence, the signal is small (≈ 1000 e -) and the radiation tolerance is much below the LHC requirements by factors of 100 to 1000. In this paper we present the development of a fully Depleted Monolithic Activ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…In [11] it was shown that depleted active pixel sensors can be made in a commercial HV CMOS technology which allows application of higher bias voltages resulting in larger depleted depths and therefore significant charge collection from drift of charge carriers which is necessary for HL-LHC environment. This was followed by several other developments in various flavours of CMOS processes resulting in prototypes of active pixel detectors with significant depleted thickness [12][13][14] which can be commonly named as depleted CMOS pixels [15]. Recent irradiation study of depleted CMOS pixels irradiated with reactor neutrons up to HL-LHC fluence was published in [16].…”
Section: Introductionmentioning
confidence: 99%
“…In [11] it was shown that depleted active pixel sensors can be made in a commercial HV CMOS technology which allows application of higher bias voltages resulting in larger depleted depths and therefore significant charge collection from drift of charge carriers which is necessary for HL-LHC environment. This was followed by several other developments in various flavours of CMOS processes resulting in prototypes of active pixel detectors with significant depleted thickness [12][13][14] which can be commonly named as depleted CMOS pixels [15]. Recent irradiation study of depleted CMOS pixels irradiated with reactor neutrons up to HL-LHC fluence was published in [16].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the fall time, the switched reset flavour was developed. Switched reset pixels have been explored in previous works, but the reset frequency was limited to the speed of the clock signal that is used to control the switched feedback current [14]. The outputs of the CSA and of the comparator of all the pixels of the matrix can be read out via dedicated pads or through an analogue buffer.…”
Section: Pos(vertex2019)019mentioning
confidence: 99%
“…The depth of the depleted sensing volume can be approximately described by d ∝ √ ρ V , where d is the depletion depth, ρ is the resistivity of substrate and V the bias voltage. Thus, it is natural for CMOS pixels to utilize the high resistivity and high voltage features steadily offered by the commercial CMOS processes [10,11]. In this section, the two design approaches we have been following to achieve a fully depleted sensing layer are described.…”
Section: Sensor Design Approachesmentioning
confidence: 99%